Total and regional fat‐to‐muscle mass ratio and risks of incident all‐cause dementia, Alzheimer's disease, and vascular dementia. Issue 5 (20th July 2022) - Wang, Wenxiu; Luo, Yongchun; Zhuang, Zhenhuang; Song, Zimin; Huang, Ninghao; Li, Yueying; Dong, Xue; Xiao, Wendi; Zhao, Yimin; Huang, Tao
Abstract: Background: The fat‐to‐muscle mass ratio (FMR), which integrates the antagonistic effects of fat and muscle mass, has been proposed as a useful indicator to assess disease risk independent of overall obesity. However, little is known about the association between FMR and dementia risk. We aimed to prospectively investigate the sex‐specific associations between total and regional FMR and incident dementia. Methods: A total of 491 420 participants (223 581 men and 267 839 women; mean age 56.7 ± 8.2 and 56.3 ± 8.0 years old, respectively) free of dementia at baseline from the UK Biobank were included. Fat mass and muscle mass were measured using a bioelectrical impedance assessment device. Cox regression analyses were used to examine the associations of total and regional FMR with incident all‐cause dementia, Alzheimer's disease (AD) and vascular dementia (VD). The shape of the associations of the continuous scale of FMR and incident dementia were examined using restricted cubic spline analysis. Results: During a median 8.65 years of follow‐up, we documented 2 225 incident all‐cause dementia cases, including 836 AD and 468 VD cases. There was an L‐shaped association between whole body FMR and all‐cause dementia risk in both sexes after adjusting body mass index (BMI) and other covariates ( P for non‐linear <0.001 in men and women), where all‐cause dementia risk decreased steeply with increasing FMR and levelled off at around the medians (0.35 in men, 0.61 in women) with a hazard ratio (HR) of 0.78 (95% CI: 0.64, 0.96; P  = 0.019) and 0.60 (0.47, 0.77; <0.001) per 1 standard deviation (SD) increase in men and women, respectively. Compared with other body parts, FMR of the leg showed the strongest inverse associations [HR (95% CI; P ) per 1 SD below the medians: 0.60 (0.48, 0.75; <0.001); 0.61 (0.47, 0.79; <0.001) in men and women, respectively]. Specifically, the inverse associations of whole body FMR on all‐cause dementia risk were significant only among participants over the age of 60 ( P for trend <0.001). Multivariable adjusted Cox models showed inverse associations of whole body FMR with AD in men only ( P for trend = 0.003), whereas no statistically significant decrease was detected in VD among men and women. Conclusions: Our analyses provide strong evidence for L‐shaped associations of total and regional FMR with the development of dementia among participants aged 60 years or older independent of overall obesity.